Injuries and risk factors in professional football players during four consecutive seasons - Smpokos, E.; Mourikis, C.; Theos, C.; Manolarakis, G.; Linardakis, M. (Sport Sciences for Health, 2022)
Purpose Few studies include data from different consecutive seasons to assess specific trends in injury risk over time. The current study aimed to investigate the presence and risk factors of injuries in professional football (soccer) players during four consecutive seasons.